2017
DOI: 10.1038/gt.2017.22
|View full text |Cite
|
Sign up to set email alerts
|

MnSOD mediated by HSV vectors in the periaqueductal gray suppresses morphine withdrawal in rats

Abstract: Morphine appears to be the most active metabolite of heroin; therefore, the effects of morphine are important in understanding the ramifications of heroin abuse. Opioid physical dependence (withdrawal response) may have very long-lasting effects on the motivation for reward, including the incubation of cue-induced drug-seeking behavior. However, the exact mechanisms of morphine withdrawal (MW) are not clear yet, and its treatment remains elusive. Periaqueductal gray (PAG) is one of the important sites in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…SOD-mimetic-agent-injection attenuated the effects of morphine on mitochondrial SOD activity (Motaghinejad et al, 2015b). MnSOD overexpressed by recombinant herpes simplex virus in the periaqueductal gray of morphine-withdrawn rats suppressed the upregulated mitochondrial superoxide and the activation of endoplasmic reticulum stress (Iida et al, 2017). Numerous studies have demonstrated that exogenous agents providing antioxidant activity could also inhibit the action of morphine.…”
Section: Maintaining Redox Balance Inhibits Morphine Actionmentioning
confidence: 99%
“…SOD-mimetic-agent-injection attenuated the effects of morphine on mitochondrial SOD activity (Motaghinejad et al, 2015b). MnSOD overexpressed by recombinant herpes simplex virus in the periaqueductal gray of morphine-withdrawn rats suppressed the upregulated mitochondrial superoxide and the activation of endoplasmic reticulum stress (Iida et al, 2017). Numerous studies have demonstrated that exogenous agents providing antioxidant activity could also inhibit the action of morphine.…”
Section: Maintaining Redox Balance Inhibits Morphine Actionmentioning
confidence: 99%
“…[35] Gene therapy that involved ar ecombinant adeno-associated virus 2-mediated MnSOD, reduced acute skin injury greatly after administering as ingle dose of irradiation using 30 or 35 Gy. [40] Epperly et al,r eported that MnSOD plasmid liposomeg ene therapy reduced lipid peroxidationt hat is stimulated by radiation in the mouseo esophagus. [37] In vitro, adenoviral MnSOD aloned id not affect SCC-25 or HCPC-1 cell viability, but in combination with BCNU (a GPx andc atalase inhibitor) a synergistic increase in cell death was observed.…”
Section: Potential Applications Of Mnsod In Therapeuticsmentioning
confidence: 99%
“…Such as tudy may provide an ew therapyt om orphine physicalwithdrawal response. [40] Epperly et al,r eported that MnSOD plasmid liposomeg ene therapy reduced lipid peroxidationt hat is stimulated by radiation in the mouseo esophagus. [41] In addition, intraorala dministration of SOD-plasmid/liposomes prevented mice from radiation-induced mucositis, while still exposing the orthotopically transplanted tumour to radiation damage.…”
Section: Potential Applications Of Mnsod In Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our unpublished data shows that MW increased the mitochondrial superoxide in the vlPAG and super-oxidative scavenger reduced MW behavioral response. We reported that herpes simplex viral vector over-expressing MnSOD in the vlPAG reduced MW behavioral response 69 . It is highly possible that Sirt3 mediated by the lentiviral vector suppressed MW behavioral response through activating MnSOD.…”
Section: Discussionmentioning
confidence: 92%